English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x-y+2x=4
x -3z=1
2y-z=-15

2006-09-16 11:22:44 · 4 answers · asked by Danielle D 1 in Science & Mathematics Mathematics

4 answers

x-y+2z=4............(1)
x -3z=1...............(2)
2y-z=-15.............(3)
(1)-(2)
-y+5z=3 times 2
-2y+10z=6 add (3)
9z=-9 z=-1
x+3=1 x=-2
2y+1=-15
y=-8
x=-2,y=-8 and z=-1

2006-09-16 11:34:28 · answer #1 · answered by raj 7 · 1 0

3 equations, 3 variables - no problem. Since the last two equations only have two variables in them, use them to solve for x or y.

x - 3z = 1
x = 3z + 1

2y - z = -15
2y = z - 15
y = (1/2)z - (15/2)

take these values for x and y and put them into the first equation.

x - y + 2x = 4
(3z + 1) - ((1/2)z - (15/2) + 2((1/2)z - (15/2)) = 4

now you have 1 equation, 1 variable
solve for z, and use that to find x and y with the other equations

2006-09-16 11:35:12 · answer #2 · answered by Giovanni McAdoo 4 · 0 0

I'm assuming you meant to type

x - y + 2z = 4
x - 3z = 1
2y - z = -15

x - 3z = 1
x = 3z + 1

(3z + 1) - y + 2z = 4
3z + 1 - y + 2z = 4
5z + 1 - y = 4
-y = -5z + 3
y = 5z - 3

2y - z = -15
2(5z - 3) - z = -15
10z - 6 - z = -15
9z - 6 = -15
9z = -9
z = -1

y = 5(-1) - 3
y = -5 - 3
y = -5 + (-3)
y = -8

x = 3(-1) + 1
x = -3 + 1
x = -3 - (-1)
x = -2

z = -1
y = -8
x = -2

2006-09-16 11:50:11 · answer #3 · answered by Sherman81 6 · 1 0

x = 3z + 1
2y - 3x - 1 = -15
x - y + 2x = 4
3x - 4 = y
2(3x - 4) - 3x - 1 = -15
6x - 8 - 3x - 1 = -15
3x = -6
x = -2 ,therefore
-2 - y + 2(-2) = 4
-2 - 4 - 4 = y
-10 = y ,therefore
2(-10) - z = -15
-20 + 15 = z
-5 = z

2006-09-16 11:32:19 · answer #4 · answered by Bird 2 · 0 1

fedest.com, questions and answers